Mind, Mortality and Material Being - Anders, Paul C. (Sophia, 2011)
Many religiously minded materialist philosophers have attempted to understand the doctrine of the survival of death from within a physicalist approach. Their goal is not to show the doctrine false, but to explain how it can be true. One such approach has been developed by Peter van Inwagen. After explaining what I call the duplication objection, I present van Inwagen’s proposal and show how a proponent might attempt to solve the problem of duplication. I argue that the very features of the view that aid the proponent in responding to the duplication objection entails the possibility of an impossible state of affairs—that two distinct persons can at the same time be identical with the same bundle of material simples. The religiously minded materialist is caught between the horns of a dilemma. One’s view regarding human persons must be robust enough to account for personal identity over time, and so not fall to the duplication objection. At the same time, the view must not entail the possibility of two persons temporarily having complete coincident existence.